Analisis SWOT Dalam Menentukan Strategi Kompetitif Pada BPR Rama Ganda - Vina Islami; Rani Rani; Syahrir Syahrir (Journal of Business and Economics Research (JBE), 2022)
Global competition requires a company to continue to pay attention to market conditions and compete more competitively. Competitive strategy is one way to find competitiveness in each force. The purpose of this study was to find a competitive strategy at the Rural Bank (BPR) Rama Ganda in order to find out the strengths, weaknesses, opportunities and threats faced by the company in maintaining its survival. Type The research method used is descriptive qualitative. This research was conducted using the SWOT method by conducting IFAS analysis to analyze internal factors, EFAS analysis for external factors. The results showed that the right strategy applied by BPR Rama Ganda was the SO strategy. SO strategy with emphasis on expansion and promotion strategies. BPR Rama Ganda uses a promotional strategy through various activities. These activities are in the form of raffles and socialization. The lottery is intended for customers who use savings and time deposits products. In addition to the lucky draw, BPR Rama Ganda also conducted outreach activities to the MSME markets and communities in Bogor and related institutions to increase the number of customers. BPR Rama Ganda has a socialization program. The socialization program is an introduction to the products of BPR Rama Ganda.